Urban Resettlement Policies in Cairo: A Case Study of Manshaiat Nasser and Asmarat City - Abouzied, Roshan (AUC Knowledge Fountain, 2023)
Egypt has a long history of urban development efforts. These efforts have provided substantial solutions in providing the urban population with adequate housing opportunities, especially those living in slum areas. However, these policies have not offered optimal solutions for all residents of informal areas, and recently governments have resorted to evictions and resettlement as one of the main strategies for removing unsafe informal areas. These strategies have had a diversity of consequences on the urban planning of cities like Cairo and repercussions on community dynamics and community social fabric. Accordingly, this thesis demonstrates the impact and reflects the consequences of resettlement and relocation policies both internationally and in the case of Egypt. This thesis adopts a qualitative approach and focuses on Cairo as a case study, particularly the policy of relocating Manshaiat Naser dwellers to the Asmarat new housing project. Qualitative interviews were conducted among government officials and experts on informality, representatives working in international organizations, and community members. The findings of the thesis analyze the visions of urban policy makers toward slums, which consider relocation as one of the main drivers of the urban development of new communities. The study also reports on the effectiveness of relocation policies, the adaptability of communities to their new homes, in addition to the perspectives of residents who have been left behind in their old neighborhoods. Thus, this study highlights the degree of sustainability in dealing with the slum challenges, specifically when creating a new urban community. Finally, policy recommendations are suggested to provide a sustainable outcome for relocation projects for the dwellers and the urban environment.